Optical probe design for continuous wave near-infrared spectroscopy - Evcil, Kadir. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2009., 2009)
The modern medicine is using optical methods more and more every day, among optical methods Near-infrared Spectroscopy is one of the most appealing techniques. Near-infrared spectroscopy is a noninvasive, safe, reliable technique. With near-infrared spectroscopy even three dimensional images can be produced and functional information can be achieved. Near infrared spectroscopy uses light at the infrared portion of the electromagnetic spectrum and measures the changes in the intensity of the light. This M.S. thesis is focused on the development of a prototype Near Infrared Spectroscopy instrument. This instrument is based on the Continuous Wave Near- Infrared Spectroscopy. This system is designed by using leds that emit near-infrared light, photodiode detectors that are sensitive to near-infrared light, and operational ampli ers. The instrument's circuit design is based on the analog circuit design. The ability and e ectiveness of the system is tested on phantom and human subjects with several experiments.|Keywords: Functional, Near, Infrared, Spectroscopy, Continuous Wave, Muscle, Optical, Imaging.
Keywords: Near infrared spectroscopy.; Optical images.